(untitled) (Scientific journal of the Fergana State University, 2023)
The typological study of languages is increasingly becoming one of the leading areas of modern linguistics. The purpose of this article is to describe the linguoculturological features of the component "dog / it / sag / dog" as part of idiomatic expressions, proverbs and sayings of the Russian, Uzbek, Tajik and English languages. Hypothetically, it can be assumed that in each of these languages the concept of the zoonym word “dog” has been sufficiently studied, however, in terms of comparing four languages of different systems, the materials have not been fully studied. In the course of the study, a descriptive and comparative method, as well as methods of component and statistical analysis of idioms and paremias around this concept sphere were applied. The work carried out a component and comparative analysis of the semantic structure of clichéd units with the zoonym word “dog”, functioning in four unrelated languages, and also identified examples of their correspondence in languages of different systems. Conclusions on the study: the frequency of cliched units with the component “dog/it/sag/dog” in all compared languages indicates that this animal, due to its multifunctionality, occupies a special place in human life; positive connotations express precisely those phraseological units that directly characterize the qualities of the animal itself, and negative meanings are observed in the semantics of idiomatic expressions describing the negative qualities of a person. Within the studied languages, there are less similarities and more discrepancies in the meanings of figurative expressions with the name of a given animal, which is explained by the heterogeneity of the nature of these languages and the originality of the mentality of these peoples.